The Impact of Job Burnout on Employees’ Safety Behavior Against the COVID-19 Pandemic: The Mediating Role of Psychological Contract - Liu, Hui; Du, Yuexin; Zhou, Huiwen (Frontiers in Psychology, 2022)
Employee safety behavior is critical for occupational health in work environments threatened by the COVID-19 pandemic. Meanwhile, the widespread and increasingly serious job burnout of employees is a complex and difficult problem for enterprises to handle during any epidemic. Therefore, it is helpful to identify and discuss job burnout and other main psychological factors that affect safety behavior to find appropriate solutions. Using the PLS-SEM method, the study explored the relationship between job burnout and safety behaviors against the epidemic, as well as the mediating role of psychological contracts. According to the local guidelines for controlling COVID-19, this study revised the safety behavior scale. Data were collected by structured questionnaires in June 2020 from Chinese employees (N＝353) who resumed their work after the outbreak of the pandemic. The findings confirmed that job burnout has a negative impact on safety behavior, and psychological contracts play a partial mediating role in mitigating the negative impact. Specifically, the transaction dimension and relationship dimension of psychological contracts negatively affected safety behavior while the development dimension of the psychological contracts was not directly related to safety behaviors. It is suggested that enterprises should adopt effective measures to reduce the job burnout of employees and implement flexible psychological contract management and intervention so as to effectively improve job safety behavior performance. Based on the multidimensional model, the findings of this study shed light on promoting safety behavior to prevent the spread of epidemics.